2015
DOI: 10.3389/fneur.2014.00281
|View full text |Cite
|
Sign up to set email alerts
|

Early Intervention to Improve Hand Function in Hemiplegic Cerebral Palsy

Abstract: Children with hemiplegic cerebral palsy often have marked hand involvement with excessive thumb adduction and flexion and limited active wrist extension from infancy. Post-lesional aberrant plasticity can lead to progressive abnormalities of the developing motor system. Disturbances of somatosensory and visual function and developmental disregard contribute to difficulties with hand use. Progressive soft tissue and bony changes may occur, leading to contractures, which further limit function in a vicious cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 114 publications
1
40
0
3
Order By: Relevance
“…A case notes review covering a 10 year period [25], a national survey of therapist management of perinatal stroke undertaken by our group (under submission) and reviews of the literature [23, 26] all indicated the lack of any standardised therapy approach for perinatal stroke in the first 6 months of life, though there is current research into modified constraint [27] and action-observation [28, 29] approaches starting from around 3 months of age in infants with emerging motor asymmetries regardless of aetiology. Despite the obvious challenges in delivery, the basic science literature from neurophysiological [30, 31], animal [32] and behavioural [33] studies suggests that for infants with predominantly unilateral stroke who are at risk of unilateral cerebral palsy, early intervention could improve long-term motor outcome.…”
Section: Introductionmentioning
confidence: 99%
“…A case notes review covering a 10 year period [25], a national survey of therapist management of perinatal stroke undertaken by our group (under submission) and reviews of the literature [23, 26] all indicated the lack of any standardised therapy approach for perinatal stroke in the first 6 months of life, though there is current research into modified constraint [27] and action-observation [28, 29] approaches starting from around 3 months of age in infants with emerging motor asymmetries regardless of aetiology. Despite the obvious challenges in delivery, the basic science literature from neurophysiological [30, 31], animal [32] and behavioural [33] studies suggests that for infants with predominantly unilateral stroke who are at risk of unilateral cerebral palsy, early intervention could improve long-term motor outcome.…”
Section: Introductionmentioning
confidence: 99%
“…In Western countries, determining the trajectory of hand development can only be considered in the context of infants already receiving some kind of early intervention or involvement in research interventions. New knowledge of increased plasticity of the young brain indicates that early intensive intervention might be more effective than later treatment and enhances development of the neuromotor system …”
mentioning
confidence: 99%
“…New knowledge of increased plasticity of the young brain indicates that early intensive intervention might be more effective than later treatment and enhances development of the neuromotor system. [5][6][7] Early development for children at high risk of CP has previously been described for reaching, in which children demonstrate some development over time but with reduced kinematic quality than typically developing children. 8,9 For older children with unilateral CP, from 18 months of age, the ability to use the impaired hand in bimanual activities has been described and it increases over time, but to a varying extent depending on the child's initial ability.…”
mentioning
confidence: 99%
“…Early intervention influencing reorganisation could be beneficial or harmful 17. While there is some evidence of benefit in the literature for ‘baby CIMT’, there remains important questions with respect to a safe time window.…”
Section: Managementmentioning
confidence: 99%